A water-based method for measuring density-based partition curves of separators used in coal and mineral processing. (August 2015) - Iveson, S.M.; Hunter, D.M.; Galvin, K.P.
Graphical abstract: Density partition curve measurements: Comparison of new fractionation method using aqueous glycerol solutions in a laboratory Reflux Classifier versus standard sink–float method using hazardous heavy organic liquids. Highlights: Feed, product and reject samples were collected around full-scale unit operations. Each sample was fractionated in a laboratory Reflux Classifier. From the yield–ash curves, the density distribution was inferred. The resultant partition curves were in close agreement with sink–float results. So the Reflux Classifier is a potential alternative to the sink–float method. Abstract: Traditional sink–float methods for measuring the density distribution of particulate samples rely on expensive and toxic heavy liquids. An alternative method has been developed which uses aqueous glycerol solutions in a laboratory-scale Reflux Classifier run in semi-batch mode. The high viscosity of these solutions promotes laminar high-shear flow in the channels which suppresses the effect of particle size on separation performance. Thus this technique was able to accurately measure the yield–ash curve of coal samples, and from this their density distribution could be inferred. Applying this approach to feed, product and reject samples enabled calculation of the density partition separation performance. Samples were collected from two case studies: a laboratory-scale continuous Reflux Classifier and a single spiral start from a full-scale coal handling and preparation plant. In both cases the partition curve measured by the new method was within experimental uncertainty of the partition curve measured by the standard sink–float method.